Clinical Factors Associated with Sperm DNA Fragmentation in Male Patients with Infertility. (3rd August 2014) - Komiya, Akira; Kato, Tomonori; Kawauchi, Yoko; Watanabe, Akihiko; Fuse, Hideki
Abstract : Objective . The clinical factors associated with sperm DNA fragmentation (SDF) were investigated in male patients with infertility. Materials and Methods . Fifty-four ejaculates from infertile Japanese males were used. Thirty-three and twenty-one were from the patients with varicoceles and idiopathic causes of infertility, respectively. We performed blood tests, including the serum sex hormone levels, and conventional and computer-assisted semen analyses. The sperm nuclear vacuolization (SNV) was evaluated using a high-magnification microscope. The SDF was evaluated using the sperm chromatin dispersion test (SCDt) to determine the SDF index (SDFI). The SDFI was compared with semen parameters and other clinical variables, including lifestyle factors. Results . The SDFI was 41.3 ± 22.2% (mean ± standard deviation) and did not depend on the cause of infertility. Chronic alcohol use increased the SDFI to 49.6 ± 23.3% compared with 33.9 ± 18.0% in nondrinkers. The SDFI was related to adverse conventional semen parameters and sperm motion characteristics and correlated with the serum FSH level. The SNV showed a tendency to increase with the SDFI. The multivariate analysis revealed that the sperm progressive motility and chronic alcohol use were significant predictors of the SDF. Conclusion . The SCDt should be offered to chronic alcohol users and those with decreased sperm progressive motility.